Prioritizing comparative effectiveness research for cancer diagnostics using a regional stakeholder approach. (May 2012) - Klein, Gregory; Gold, Laura S; Sullivan, Sean D; Buist, Diana SM; Ramsey, Scott; Kreizenbeck, Karma; Snell, Kyle; Loggers, Elizabeth Trice; Gifford, Joseph; Watkins, John B; Kessler, Larry
Aims: This paper describes our process to engage regional stakeholders for prioritizing comparative effectiveness research (CER) in cancer diagnostics. We also describe a novel methodology for incorporating stakeholder data and input to inform the objectives of selected CER studies.Materials & methods: As an integrated component to establishing the infrastructure for community-based CER on diagnostic technologies, we have assembled a regional stakeholder group composed of local payers, clinicians and state healthcare representatives to not only identify and prioritize CER topics most important to the western Washington State region, but also to inform the study design of selected research areas. A landscape analysis process combining literature searches, expert consultations and stakeholder discussions was used to identify possible CER topics in cancer diagnostics. Stakeholders prioritized the top topics using a modified Delphi/group-nominal method and a standardized evaluation criteria framework to determine a final selected CER study area. Implementation of the selected study was immediate due to a unique American Recovery and Reinvestment Act funding structure involving the same researchers and stakeholders in both the prioritization and execution phases of the project. Stakeholder engagement was enhanced after study selection via a rapid analysis of a subset of payers' internal claims, coordinated by the research team, to obtain summary data of imaging patterns of use. Results of this preliminary analysis, which we termed an 'internal analysis, ' were used to determine with the stakeholders the most important and feasible study objectives.Results: Stakeholders identified PET and MRI in cancers including breast, lung, lymphoma and colorectal as top priorities. In an internal analysis of breast cancer imaging, summary data from three payers demonstrated utilization rates of advanced imaging increased between 2002 and 2009 in the study population, with a great deal of variability in use between different health plans. Assessing whether breast MRI affects treatment decisions was the top breast cancer study objective selected by the stakeholders. There were other high-priority research areas including whether MRI use improved survival that were not deemed feasible with the length of follow-up time following MRI adoption.Conclusion: Continuous stakeholder engagement greatly enhanced their enthusiasm for the project. We believe CER implementation will be more successful when undertaken by regional stakeholders.